Challenges Faced by Families of Children with Intellectual Disabilities and Its Effect on the Psychological Health in the Asir (Journal Of Educational and Psychological Researches, 2023)
AbstractThis research aims to identify the challenges faced by families of children with intellectual disabilities and to identify the impact of the challenges facing them on the mental health of their children with intellectual disabilities. Based on the following questions: What is the nature of the challenges faced by families of children with disabilities and how do these challenges affect the mental health of their children with intellectual disabilities? The study was conducted on a sample of four families of six children with intellectual disabilities, depending on the degree and type of disability. To achieve the study's objectives, the qualitative approach was used, Because of the importance of accessing information from its natural sources, as required by the nature of the study, the importance of knowing some of the minute details, and being able to delve into the explanations about the challenges facing families with intellectual disabilities. To answer research questions. The results of the study showed that the Lack of awareness plays a major role in mental health in the lives of families and their children in a very large way. The lack of knowledge of the case, how to deal with it, and the outcome of the case affects mainly the lifestyle and mental health of families and their children. The lack of community awareness as well has a clear role in the negative impact on the lives of the families of children with intellectual, social, and educational disabilities. All the interviews in all their different aspects proved the complete need for the necessary psychological, educational, life, and medical awareness, because of their great impact on the mental health of children with intellectual disabilities, and their families.